2012
DOI: 10.1074/jbc.m111.277921
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-dependent Externalization and Involvement in Apoptotic Cell Clearance of DmCaBP1, an Endoplasmic Reticulum Protein of Drosophila

Abstract: Background: Cells undergoing apoptosis are selectively recognized and engulfed by phagocytes. Results: A Drosophila endoplasmic reticulum protein named DmCaBP1 was externalized upon apoptosis, bound to both apoptotic cells and phagocytes, and enhanced phagocytosis. Conclusion: DmCaBP1 connects apoptotic cells and phagocytes to promote phagocytosis. Significance: We are first to report that a protein residing in the endoplasmic reticulum plays a role in apoptotic cell clearance as a tethering molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Thus, we developed a simplified assay platform to dissect a complex cell signaling process that requires multiple receptors and ligands in vivo (Freeman and Grinstein, 2014). Draper is also reported to recognize the protein ligands Pretaporter and DmCaBP1 (Kuraishi et al, 2009;Okada et al, 2012) and has been reported to work in collaboration with co-receptors in flies such as Six Microns Under (SIMU) (Kurant et al, 2008) and integrins (Nagaosa et al, 2011). Our results do not rule out a role for these proteins in vivo to tune sensitivity for triggering and/or allow engulfment under low concentrations of PS (Manaka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we developed a simplified assay platform to dissect a complex cell signaling process that requires multiple receptors and ligands in vivo (Freeman and Grinstein, 2014). Draper is also reported to recognize the protein ligands Pretaporter and DmCaBP1 (Kuraishi et al, 2009;Okada et al, 2012) and has been reported to work in collaboration with co-receptors in flies such as Six Microns Under (SIMU) (Kurant et al, 2008) and integrins (Nagaosa et al, 2011). Our results do not rule out a role for these proteins in vivo to tune sensitivity for triggering and/or allow engulfment under low concentrations of PS (Manaka et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid phosphatidylserine (PS) is exposed on dying cells and is considered to be an important "eat me" signal (Fadok et al, 1992). PS was previously shown to cause Draper phosphorylation (Tung et al, 2013), but multiple protein ligands for Draper also have been suggested (Kuraishi et al, 2009;Okada et al, 2012). Based upon prior studies, it was unclear whether one or multiple ligands were needed to execute full engulfment.…”
Section: Cellular Reconstitution Of Draper-dependent Engulfmentmentioning
confidence: 99%
“…Recently in Drosophila, two proteins of the endoplasmic reticulum, Pretaporter and DmCaBP1, have been observed to become externalised in apoptosis aiding phagocytosis mediated by Draper, a fly hemocyte receptor for apoptotic cells that is homologous to CED-1. 33,34 We established that LBP/p40 translocates from its intracellular location to the plasma membrane surface during apoptosis. In light of our observations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Various proteins and lipids from the endoplasmic reticulum (ER) have also been found to be exposed at the surface of human ACs ( 62 ). Nakanishi and colleagues identified three ER proteins acting upstream of Drpr to promote phagocytosis in Drosophila ( 63 65 ). They showed that Drosophila Calr existed at the surface of living cells and reassigned to form aggregates upon apoptosis without change of the amount and expression at the cell surface; and that in a Drosophila mutant strain with reduced level of Calr, the level of phagocytosis of ACs was about a half of that observed in wild-type embryos ( 63 ).…”
Section: Bridging Moleculementioning
confidence: 99%
“…Reexpression of prtp in hemocytes did not rescue this defect while the ubiquitous expression did, which indicated that Prtp functions in ACs to promote phagocytes’ engulfment ( 64 ). The DmCaBP1 is released and externalized from ACs, to bind to the extracellular region of Drpr ( 65 ). Loss of either prtp or DmCaBP1 led to a reduced level of AC clearance in Drosophila embryos, but the double mutant did not cause a further decreased in phagocytosis, which indicated that they act in the same pathway.…”
Section: Bridging Moleculementioning
confidence: 99%